Techno-economic investigation and multi-criteria optimization of a novel combined cycle based on biomass gasifier, S-CO2 cycle, and liquefied natural gas for cold exergy usage. (August 2022) - Cao, Yan; Dhahad, Hayder A.; Hussen, Hasanen M.; ATTIA, El-Awady; Rashidi, Shima; Shamseldin, Mohamed A.; Fahad Almojil, Sattam; Ibrahim Almohana, Abdulaziz; Fahmi Alali, Abdulrhman
Highlights: A closed Brayton-Brayton combined cycle is proposed driven by biomass gasification. LNG cold exergy is used for compressor inlet cooling to below 0 °C temperature. Exergoeconomic evaluation and multi-objective optimization is presented. Negative environmental impact costs are taken into account in economic analysis. Abstract: It has long since been recognized that biomass energy can be used as a renewable source to convert chemical energy into power. In this research, a novel combined cycle is proposed for generating competent power from biomass chemical energy. Since the closed Brayton cycles have many advantages over open ones, the system is composed of two closed Brayton cycles with working fluids of nitrogen and supercritical carbon dioxide. Furthermore, to cool down the N2 compressors inlet temperatures to below 0℃, the technique of utilizing the liquefied natural gas is used. A comprehensive thermodynamic and economic study is performed, and the effect of key design variables is out posted by parametric evaluation. In a valuable procedure, the cost of the pollutants (NOx, CO, and CO2) emitted to the environment is found. Finally, to seek the best solution from the exergoeconomic aspect, the multi-criteria optimization is carried out, in which the results show that exergetic efficiency of 43.51% with a power cost of 19.78 $/GJ can be reached at the optimal point. Also, results indicate that the capital investment cost of gas turbines is higher than other elements; on the contrary, the destructed cost of the elements with chemical reactions like gasifiers and combustion chambers is the highest.